Antioxidants and α-glucosidase inhibitors from Ipomoea batatas leaves identified by bioassay-guided approach and structure-activity relationships. (1st October 2016) - Zhang, Lu; Tu, Zong-cai; Yuan, Tao; Wang, Hui; Xie, Xing; Fu, Zhi-feng
Highlights: Bioactivity-guided approach is a valuable tool for isolating active compounds. Phenethyl cinnamides and 3, 4, 5-triCQA show the best α -glucosidase inhibition. 3, 4, 5-TriCQA and diCQAs are the predominant antioxidants. Caffeoylation of quinic acid and methoxylation of flavonol improve the antioxidant activity. Methylation and cis structure weak the α -glucosidase inhibition of phenethyl cinnamides. Abstract: Sweet potato ( Ipomoea batatas ) leaf (SPL) is an underused commercial vegetable with considerable bio-activities. By means of DPPH scavenging ability and α -glucosidase inhibitory oriented isolation, 9 and 7 compounds were isolated and identified, respectively. Among them, trans - N -( p -coumaroyl)tyramine (1 ), trans - N -feruloyltyramine (2 ), cis - N -feruloyltyramine (3 ), 4, 5-feruloylcourmaoylquinic acid (8 ), caffeic acid ethyl ester (10 ), 7-hydroxy-5-methoxycoumarin (11 ), 7, 3′-dimethylquercetin (13 ) and indole-3-carboxaldehyde (15 ), were firstly identified from SPL, and four of them (1, 2, 3 and10 ) were firstly identified from genus Ipomoea . Phenethyl cinnamides and 3, 4, 5-triCQA exhibited the strongest α -glucosidase inhibition, while 3, 4, 5-triCQA and diCQAs were the dominant antioxidants. Structure-activity relationship revealed that higher caffeoylation of quinic acid and lower methoxylation of flavonols resulted in stronger antioxidant activity, and methylation and cis -configuration structure of phenethyl cinnamides weaken the α -glucosidase inhibition. Aforementioned results could help to explain the antioxidant activity and anti-diabetic activity of SPL, and provide theoretical basis for its further application.